2015
DOI: 10.14254/2071-8330.2015/8-2/6
|View full text |Cite
|
Sign up to set email alerts
|

Specialization and diversification of agricultural production in the light of sustainable development

Abstract: Abstract. Th e study evaluated the importance of agricultural production structures for economic effi ciency and environmental sustainability of farms. For this purpose, multivariate methods were used: ordering and data envelopment analysis (DEA). Th e study is based on accounting data from the farms of intensive agriculture in Wielkopolska Province, collected by the Institute of Agricultural and Food Economics in Warsaw in [2004][2005][2006][2007][2008][2009]. It was demonstrated that diversifi ed farms achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 4 publications
(2 reference statements)
1
21
0
Order By: Relevance
“…The CAP instruments are covering support for agriculture which resulted in growth the income of farms', and structural funds have increased the investment for the modernization of agriculture and food sectors and for the development of rural areas. To provide comparable indicators on the level of agricultural production that significantly increased during the period considered between all EU countries we used data of EAA (Czyżewski et al, 2015) and it is noted that specialized farms increase farm efficiency but can influence in the quality of food and use of natural resources in rural areas. As noted in the literature (Namiotko et al, 2019;Zsarnóczai et al, 2019;Střeleček et al, 2009), agricultural productivity growth in farmers' farms is related with higher investments, also the subsidies on production were focused on new technology, to increase consumption of fixed capital.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAP instruments are covering support for agriculture which resulted in growth the income of farms', and structural funds have increased the investment for the modernization of agriculture and food sectors and for the development of rural areas. To provide comparable indicators on the level of agricultural production that significantly increased during the period considered between all EU countries we used data of EAA (Czyżewski et al, 2015) and it is noted that specialized farms increase farm efficiency but can influence in the quality of food and use of natural resources in rural areas. As noted in the literature (Namiotko et al, 2019;Zsarnóczai et al, 2019;Střeleček et al, 2009), agricultural productivity growth in farmers' farms is related with higher investments, also the subsidies on production were focused on new technology, to increase consumption of fixed capital.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Order to investigate differences in investment support impacts analysed their relationship by size groups of farms and their types of farming and pointed that the number of projects are taken under the RDP is related with the size of farms. (Ratinger 2013;Czyżewski et al, 2015). Finally, they concluded that support for investment became a key tool for agricultural policy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The increasing competitiveness of the regions requires to specify distinct government priorities in investment policy of regional development by improving investment climate, defining promising sectors of economy, reconciling interests of state, region, financial institutions and business entities in relation to directions and means of transformation of investment resources, etc. (Czyżewski et al 2015;Zatonatska 2016;Cieślik et al 2016;Brodzicki 2016;or Mishenin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Current trends in agriculture development are focused not only on economic performance, but also on the consequences of corporate activities for the environment and sustainabality (Rajnoha, Lesníkova, 2016;Balas, 2014;Czyżewski, Smędzik-Ambroży, 2015).…”
Section: Introductionmentioning
confidence: 99%